ANALISIS PENCAPAIAN PREDIKAT UNGGUL PADA PROGRAM MAGISTER MPI DALAM PERSPEKTIF ISU KONTEMPORER PENDIDIKAN ISLAM - Kusharyati , Indah; Abdul Aziz; indah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the achievement of superior predicates in the Master of Islamic Education Management (MPI) Program in the perspective of contemporary issues of Islamic education. The superior accreditation not only reflects the fulfillment of national standards, but also demonstrates the institution's success in integrating Islamic values with global challenges such as digitalization, religious moderation, and managerial transformation. This study uses a qualitative approach with a case study type, focusing on one study program as an analysis unit. Data was collected through in-depth interviews, participatory observations, and document review such as accreditation reports, curriculum, and internal evaluation results. The analysis was carried out thematically with the application of triangulation of sources and methods to maintain the validity of the data. The results of the study show that the achievement of superior accreditation in the MPI Master's Program is supported by transformative leadership, an effective internal quality assurance system, curriculum innovation based on KKNI and OBE, and cross-institutional academic collaboration. In addition, the application of Islamic values in governance and learning strengthens the scientific identity and social relevance of the program. This research emphasizes that the success of superior accreditation is not only an administrative achievement, but a form of integration between academic quality management and Islamic spirituality in answering educational challenges in the contemporary era